Syntheses and photophysico-chemical properties of phthalocyanines in the presence of silica nanoparticles - Peteni, Siwaphiwe (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
This thesis reports on the syntheses and characterizationof symmetrical (charged and neutral), asymmetrical (neutral) metallophthalocyanines (MPcs) and subphthalocyanines (SubPcs). The charged and neutral Pcs were physically doped onto silica nanoparticles (SiNPs). The asymmetrical MPc was also chemically linked to SiNPs. Spectroscopic and microscopic techniques were used to confirm the formation of SiNPs-MPc conjugates. The photophysics and photochemistry of the MPcs were assessed when alone and in conjugates (with SiNPs). The studies showed no significant changes in fluorescence quantum yields (Ï•F) and fluorescence lifetimes (Ï•F) of MPcs following doping except for 2-SiNPs (2 = Zn tetraaminophenoxyphthalocyanines) and 6-SiNPs (doped) (6 = Zn tris[(4-(pyridine-4-ylthio)2-thio-4-methylthiazol-5yl) acetic acid phthalocyanine) where there was a decrease in the Ï•F value. Also for 1-SiNPs (1 = unsubstituted ZnPc) there was an elongation in Ï„F which could be due to the protection offered by SiNPs. Both charged/neutral MPcs displayed high triplet quantum yields (Ï•T) and singlet quantum yields (Ï•Î”) following doping except for 2-SiNPs where there was a decrease in the latter. For 1-SiNPs there was an increase in Ï•T but a decrease inÏ•Î” .There wasa decrease in Ï•T and an increase in Ï•Î”for4-SiNPs (4 = Zn tetrasulfophenoxyphthalocyanine), the decrease in Ï•T could be due to the orientation of theMPc in SiNPs. An increase in both Ï•T and Ï•Î” for 6-SiNPs (linked) compared to 6-SiNPs (doped) was observed. Complex 5 (5 = Zn tetra-kis-(dodecylmercapto) phthalocyanine) showed a low Ï•Î” value.
Keywords: Phthalocyanines; Silica; Nanoparticles; Bioconjugates